Pre and Post Test Clinical Study to Assess the Combined Effect of Brihatyadi Ksheera Kashaya, Chandraprabhavati and Shweta Parpati in Urinary Tract Infection - Anjana.S; Mahesh.C.Kundagol; Devipriya Soman; James Chacko (International Journal of Ayurveda and Pharma Research, 2021)
Purpose: UTI is the broad term used to describe infection of any part of urinary tract and is a problem frequently encountered by health care providers today. E.coli is found to be the main causative agent for causing UTI (80%). The prevalence of UTI are increasing and the present standard of care includes the usage of antibiotics. The alarming and exponential use of nonspecific antibiotics, increased resistance and the high cost of prescribed medications for the management of the infective microorganisms will raise the need for alternate and safe medication. The signs and symptoms of Mutrakruchra and UTI are similar in nature. The combination of Brihatyadi Ksheera Kashaya, Chandraprabhavati and Shweta Parpati is widely practiced in Mutrakruchra. The present study was aimed at exploring the combined effect of the above combination in UTI. Materials and Methods: The present study was a single group study with pre and post test study design. 20 diagnosed cases of UTI based on ICD10N39.0 diagnostic criteria and proper exclusion were selected from IPD and OPD of Amrita Ayurveda Hospital. They were administered Brihatyadi Ksheera Kashaya, Chadraprabhavati and Shweta Parpati for 15 days. Result: The obtained data were analyzed statistically with symptoms of UTI, Urine analysis and urine culture by using Wilcoxon signed rank test done on the 0th and 16th day. There was significant change with 100% of improvement in clinical symptoms of UTI after treatment. Statistically significant result was obtained in reduction of WBC with p value 0.001, Epithelial cells with p value 0.005, and Nitrites, Leucocyte esterase, Bacteria with p value 0.0001. There was reduction in growth of E.coli in urine culture with statistically significant p value 0.0001. Conclusion: The combination of Brihatyadi Ksheera Kashaya, Chandraprabhavari and Shwetaparpati is effective in UTI.